2023
DOI: 10.18502/fid.v20i16.12686
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ferrule/Crown Ratio and Post Length on the Applied Stress and Strain Distribution to the Endodontically Treated Maxillary Central Teeth: A Finite Element Analysis

Abstract: Objectives: One of the most common methods used for the reconstruction of endodontically treated teeth is post and core and crown. Various factors such as the remaining tissue above the cutting margin (ferrule) affect the fracture resistance of teeth restored with post and core and crown. This study aimed to investigate the effect of ferrule/crown ratio (FCR) on the strength of maxillary anterior central teeth using finite element analysis. Materials and Methods: A 3D scan of a central incisor was obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In a three-year clinical follow-up study, only 6.67% of incisors restored with 2 mm ferrule posts were damaged, while the rate for teeth without ferrule reached 26.20%. 19 However, in the study by Samran A. and al. conducted on mandibular premolars, the specific location of the ferrule had no significant effect on fracture resistance under the study’s conditions.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In a three-year clinical follow-up study, only 6.67% of incisors restored with 2 mm ferrule posts were damaged, while the rate for teeth without ferrule reached 26.20%. 19 However, in the study by Samran A. and al. conducted on mandibular premolars, the specific location of the ferrule had no significant effect on fracture resistance under the study’s conditions.…”
Section: Discussionmentioning
confidence: 93%
“… 18- Mosharaf R. and al. (2023) 19 (Finite Element Analysis Studies) A 3D scan of a central incisor To study the effect of the ferrule height-to-crown ratio on the strength of maxillary anterior central teeth using finite element analysis. 3D scan of a maxillary central incisor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to finite element studies, presence of ferrule yields favorable stress distribution in roots. In addition, higher ferrule would result in lower stress and consequently decrease in clinical failure [ 12 , 13 , 15 , 34 ]. It is highly favorable to provide a complete CF with a minimum height of 2 mm which improves the prognosis of ETT [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have concluded that the design of the ferrule does not exert an influence on the biomechanical performance of endodontictreated incisor teeth [10,12], there is consensus that the presence of an incomplete ferrule is considered a better option than the complete lack of it [9,13,14]. Many studies have assessed the impact of different ferrule heights [14][15][16] and the influence of the post material [1,17,18] in the development of non-reparable (below the cement-enamel junction-CEJ-leading to tooth extraction) or reparable (above CEJ) tooth fractures [8,19]. However, there are a lack of studies testing incomplete ferrule designs and their interaction with one-piece post-core made of PEEK related to the stress distribution of human maxillary incisors rehabilitated with monolithic zirconia crowns; thus, these are the parameters tested in this study.…”
Section: Introductionmentioning
confidence: 99%